Mental health and COVID-19 vaccine hesitancy among health-related university students: a cross-sectional multi-center study - Thanawat Khongyot; Amy Takyi; Dympna Siysila Ndzeshang; Karl Gwei Njuwa Fai; Tin Zar Win; Latdavanh Vorlasane; Gibson Omwansa Javes; Satoshi Kaneko; Taeko Moriyasu (Tropical Medicine and Health)
Abstract Background The mental health problems during the coronavirus disease 2019 (COVID-19) pandemic may have influenced their decision to receive the COVID-19 vaccine among health-related university students, with potential differences across countries. This study elucidated the association between mental health and COVID-19 vaccine hesitancy of health-related university students in Thailand, Laos, and Japan. We additionally examined the other factors that might relate to COVID-19 vaccine hesitancy. Methods The study conducted an online survey from February 4 to 27, 2021, among undergraduate students enrolled in health-related programs at University of Health Sciences (Lao PDR), Walailak University (Thailand), and Nagasaki University (Japan) using a non-probability convenience sampling method. The data were analyzed using multiple logistic regression to identify associations between mental health and self-reported COVID-19 vaccine hesitancy and other potential factors. Results This study analyzed data from 841 students. Japanese students attended hybrid classes (82.45%), while those in Laos and Thailand had entirely online courses. All mental health assessment scores (depression, anxiety, and stress) were higher in Thailand and Laos compared to Japan. Students with very high-stress scores had the highest odds of vaccine hesitancy (aOR 2.67, 95% CI 1.45–4.93). Fear of COVID-19 increased hesitancy, while unbelief in vaccine protection significantly increased it (aOR 2.59, 95% CI 1.86–3.59). Females displayed about two times greater hesitancy (adjusted odds ratio, aOR 2.43, 95% CI 1.68–3.51), which correlated with higher mental health scores. Conclusions We highlighted a significant association between mental health and self-report COVID-19 vaccine hesitancy. Interventions, including tailored support, awareness campaigns, and psychological services, can foster trust and vaccine uptake.